The phenomenon of the symbol in the space of everyday life - Staskevich, Sergey A. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The aim of the article is to identify the role of the symbol in the space of virtual everyday life. Virtual everyday life is understood as a double isolation of presence, both in relation to its own authentic existence and to the publicity formed in crowds (popular superficial opinions of idle curiosity). It is substantiated that in modern conditions this isolation is connected with the phenomenon of the symbol, which, being a sign with inexhaustible semantic potential, allows presence to keep itself in the status of success. Status is one of the ways in which the identity of presence is held in the symbol. The identity of presence, in turn, is characterised by the competence that presence has assumed for itself as the most comfortable competence. Thus, the comfortable competence of presence is the basis of modern publicity and, having passed from identity to status, leads to social anomie and radical individualism.
Keywords: symbol; publicity; everyday life; modernity; comfort; competence; identity; status; M. Heidegger